Variation in oxygen isotope ratio of dissolved orthophosphate induced by uptake process in natural coral holobionts - Ferrera, Charissa M.; Miyajima, Toshihiro; Watanabe, Atsushi; Umezawa, Yu; Morimoto, Naoko; San Diego-McGlone, Maria Lourdes; Nadaoka, Kazuo (Coral reefs, 2016)
A model incubation experiment using natural zooxanthellate corals was conducted to evaluate the influence of phosphate uptake by coral holobionts on oxygen isotope ratio of dissolved PO 4 3− (δ 18 O p ). Live coral samples of Acropora digitifera, Porites cylindrica, and Heliopora coerulea were collected from coral reefs around Ishigaki Island (Okinawa, Japan) and Bolinao (northern Luzon, Philippines) and incubated for 3–5 d after acclimatization under natural light conditions with elevated concentrations of PO 4 3– . Phosphate uptake by corals behaved linearly with incubation time, with uptake rate depending on temperature. δ 18 O p usually increased with time toward the equilibrium value with respect to oxygen isotope exchange with ambient seawater, but sometimes became higher than equilibrium value at the end of incubation. The magnitude of the isotope effect associated with uptake depended on coral species; the greatest effect was in A. digitifera and the smallest in H . coerulea . However, it varied even within samples of a single coral species, which suggests multiple uptake processes with different isotope effects operating simultaneously with varying relative contributions in the coral holobionts used. In natural environments where concentrations of PO 4 3– are much lower than those used during incubation, PO 4 3– is presumably turned over much faster and the δ 18 O p easily altered by corals and other major primary producers. This should be taken into consideration when using δ 18 O p as an indicator of external PO 4 3– sources in coastal ecosystems.